2011
DOI: 10.1136/vr.d2671
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic changes after gonadectomy in retired racing greyhounds

Abstract: Twenty-one healthy greyhounds with no history or clinical signs of bleeding disorders, and no abnormalities on physical examination, complete blood count, serum biochemistry profiles (in dogs more than five years of age), and SNAP-4DX test for vector borne diseases underwent routine gonadectomies at the Ohio State University Veterinary Teaching Hospital. Blood samples were collected 24 hours before and after surgery by jugular venepuncture for thromboelastography and haemostasis assays (prothrombin time [PT], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…The α angle has similar behavior and a similar explanation to the increased MCF; it significantly increased from T0 to T2 in the in‐TEM assay and in the ex‐TEM assay. These findings are similar to those reported by Vilar Saavedra and others, who demonstrated that TEG parameters representing fibrin cross‐linking (α angle) and clot strength (maximum amplitude) increase after gonadectomy in retired racing Greyhounds . In human patients undergoing a wide variety of surgical procedures, the risk of deep venous thrombosis was significantly higher in patients with a TEG maximum amplitude >68 mm, establishing a putative cutoff to assess the risk for the development of this complication …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The α angle has similar behavior and a similar explanation to the increased MCF; it significantly increased from T0 to T2 in the in‐TEM assay and in the ex‐TEM assay. These findings are similar to those reported by Vilar Saavedra and others, who demonstrated that TEG parameters representing fibrin cross‐linking (α angle) and clot strength (maximum amplitude) increase after gonadectomy in retired racing Greyhounds . In human patients undergoing a wide variety of surgical procedures, the risk of deep venous thrombosis was significantly higher in patients with a TEG maximum amplitude >68 mm, establishing a putative cutoff to assess the risk for the development of this complication …”
Section: Discussionsupporting
confidence: 89%
“…In brief, the MCF of the fib‐TEM assay (which is related to the functional fibrinogen concentration) was the only variable to significantly increase for each comparison. The changes observed in MCF are likely related to postoperative increases in fibrinogen concentration, a consistent postoperative finding in people . The α angle has similar behavior and a similar explanation to the increased MCF; it significantly increased from T0 to T2 in the in‐TEM assay and in the ex‐TEM assay.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In 1 study, the G value calculated from tissue factor‐activated TEG had a positive predictive value of 89% and a negative predictive value of 98% in identifying bleeding tendencies . In a separate study limited to greyhounds, MA, angle, and G predicted postoperative bleeding tendencies . Lastly, in a recent study, TEG was reliable in identifying thrombocytopenic dogs to be at a low risk of bleeding .…”
Section: Discussionmentioning
confidence: 93%
“…In addition, they are known to have a higher PCV, resulting in higher blood viscosity, and a lower platelet count . Some Greyhounds are also known to have significant postoperative bleeding, which may be related to increased fibrinolysis or reduced fibrin cross‐link formation and clot strength . Despite postoperative bleeding, PCTs were found to be normal in one study .…”
Section: Discussionmentioning
confidence: 97%